The ciliary GTPase Arl13b regulates cell migration and cell cycle progression. Issue 4 (3rd July 2016) - Pruski, Michal; Rajnicek, Ann; Yang, Zhifu; Clancy, Hannah; Ding, Yu-Qiang; McCaig, Colin D.; Lang, Bing
ABSTRACT: The GTPase ARL13B is localized to primary cilia; small cellular protrusions that act as antennae. Its defective ARL13B hennin (HNN) variant is linked causally with Joubert Syndrome, a developmental ciliopathy attributed to poor sensing of extracellular chemical gradients. We tested the hypothesis that impaired detection of extracellular voltage gradients also contributes to the HNN phenotype. In vitro, extracellular electric fields stimulated migration of wild type (WT) and HNN fibroblasts toward the cathode but the field only increased the migration speed of WT cells. Cilia on WT cells did not align to the field vector. HNN cells divided more slowly than WT cells, arresting at the G2/M phase. Mechanistically, HNN cells had reduced phospho-ERK1/2 signaling and elevated levels of Suppressor of Fused protein. These suggest that cells may not be able to read extracellular chemical cues appropriately, resulting in deficits in cell migration and proliferation. Finally, an increase in tubulin stabilization (more detyrosinated tubulin) confirmed the general stagnation of HNN cells, which may further contribute to slower migration and cell cycle progression. We conclude that Arl13b dysfunction resulted in HNN cell stagnation due to poor growth factor signaling and impaired detection of extracellular electrical gradients, and that the role of Arl13b in cell proliferation may be understated.